LITERASI BACA TULIS DALAM PEMBELAJARAN BAHASA INDONESIA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA RA ROHMATAN LIL’ALAMIN DONOREJO KARANGTENGAH DEMAK - Sabichatul Lamiah; Umi Faizah (STPI Bina Insan Mulia Yogyakarta, 2024)
This research aims to determine reading and writing literacy activities in Indonesian language learning to improve RA students' critical thinking abilities and what the supporting and inhibiting factors are. The research method used in this research is a qualitative research method with a descriptive approach, because the data analyzed in this research is descriptive data in the form of documents about reading and writing literacy in Indonesian language learning to improve RA students' critical thinking skills. Qualitative methods are research in which the researcher is the main tool, data source sampling aims to collect triangulation data techniques, inductive data analysis, and qualitative research results. From the results of research that has been carried out, reading and writing literacy in Indonesian language learning to improve students' critical thinking skills at RA Rohmatan Lil'alamin Donorejo Karangtengah Demak obtained an average score of 61.73. It is known that students' enthusiasm for reading and writing literacy activities is quite good and critical thinking skills at RA Rohmatan Lil'alamin Donorejo Karangtengah Demak are quite good, this is proven when students are able to understand, explain, conclude and solve problems. The supporting factors are cooperation between teachers and students as well as facilities in the form of adequate facilities and infrastructure. Meanwhile, the inhibiting factors are laziness and the absence of the role of parents in the learning process.